2010
DOI: 10.1111/j.1601-0825.2009.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the oral bacterial flora: current status and future directions

Abstract: Oral Diseases (2010) 16, 136–145 Objective:  The oral cavity forms an indispensable part of the human microbiome, for its unique and diverse microflora distributed within various niches. While majority of these organisms exhibit commensalism, shifts in bacterial community dynamics cause pathological changes within oral cavity and distant sites. The aim of this review was to appraise the current and emerging methods of detecting bacteria of the oral cavity paying particular attention to the cultivation independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 75 publications
0
75
0
3
Order By: Relevance
“…The assessment of the human microbioma by metagenomic approaches revealed that these techniques are sensitive and specific (6,11) to evaluate the bacterial diversity of root canal infections (10,(12)(13)(14)(15). These studies have shown that the prevalence of yet non-cultivable bacteria remarks over 50% of the microbiota in primary endodontic infections (10,14), in persistent periradicular lesions (15), or in mixed endodontic infections (16).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The assessment of the human microbioma by metagenomic approaches revealed that these techniques are sensitive and specific (6,11) to evaluate the bacterial diversity of root canal infections (10,(12)(13)(14)(15). These studies have shown that the prevalence of yet non-cultivable bacteria remarks over 50% of the microbiota in primary endodontic infections (10,14), in persistent periradicular lesions (15), or in mixed endodontic infections (16).…”
mentioning
confidence: 98%
“…Most data on the endodontic microbiota were obtained by culture approaches (3)(4)(5), but culture-dependent methods grossly underestimate the extent of bacterial diversity in polymicrobial infections (6). Furthermore, phenotypic profiles variations and methodological bias also limit the conclusions drawn from culture studies (7).…”
mentioning
confidence: 99%
“…Therefore, the skin and the upper respiratory tract are the primary GAS contact sites on new human hosts (18). Both anatomic sites are physiologically inhabited by several dozen (skin) to several hundred (respiratory tract) different bacterial species (19)(20)(21)(22)(23), of which the majority can only be demonstrated by molecular techniques (24,25). Many of these species have probiotic potential that could be exerted by biofilm formation on anatomical sites serving as targets for pathogenic bacteria.…”
mentioning
confidence: 99%
“…However, an inherent limitation of microbiological cultures is that the difficulties to identify strict anaerobes, frequently associated with periodontal and peri-implant diseases, as well as fastidious species Roças et al, 2010). It is estimated that 50% of the oral microbiota is not cultured by conventional methods and several of these species are directly related to infectious processes in the oral cavity (Arank et al, 1969;Paster et al, 2001;Parahitiyawa et al, 2010). Furthermore, non-viable cells, still able to produce aggressive compounds against peri-implant tissues are not detected by culture methods.…”
Section: Conventional Culturesmentioning
confidence: 99%